Investigating the instructors' attitudes towards the use of information and communication technologies (ICT) in higher education - Akşit, Osman. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
The aim of this study is to investigate the instructors’ attitudes towards the use of ICT in education and to explore differences in the attitudes between instructors who are grouped according to six demographic variables: age, gender, academic rank, academic discipline, years of teaching experience and location of current occupation. After an extensive review of literature, a web-based online questionnaire was prepared. The questionnaire was sent to 5646 people via e-mail. 302 instructors from twenty one different universities across Turkey have responded to the questionnaire. The response rate to the survey is 5.35%. The responses to the survey were analyzed by using IBM SPSS Statistics version 21 for Windows; reliabilities were tested by Cronbach’s Alpha analysis. Independent sample t-test and one-way ANOVA were applied to determine the differences in the attitudes towards the use of ICT in education between instructors who are grouped according to six demographic variables. The findings indicate that the instructors’ attitudes towards the use of ICT in education are positive. The findings also show that there is no statistically significant difference between instructors with different demographic characteristics of age, gender, academic rank and location of current occupation in terms of their attitudes towards the use of ICT in education. However, the findings show that there is a statistically significant difference in the attitudes towards ICT between instructors with different years of teaching experience. Limitations and suggestions for future research have been discussed at the end the study.
Keywords: Education, Higher -- Information technology.; Information technology -- Study and teaching (Higher); College teaching.